Accountability and Reform in the Aftermath of the Westray Mine Explosion - Tucker, Eric (Working Disasters: The Politics of Recognition and Response, 2006)
This edited collection draws together original case studies written by leading researchers in Australia, Canada, Great Britain, Sweden, and the United States that examine the politics of working disasters. The essays address two fundamental questions: what gets recognized as a work disaster? And how does the state respond to one? --Publisher's description. Contents: Introduction: The Politics of Recognition and Response / Eric Tucker -- Trucking Tragedies: The Hidden Disaster of Mass Death in the Long-Haul Road Transport Industry / Michael Quinlan, Claire Mayhew, and Richard Johnstone -- The Australian Epidemic of Repetition Strain Injury: A Sociological Perspective / Andrew Hopkins -- "All Part of the Game": The Recognition of and Response to an Industrial Disaster at the Fluorspar Mines, St Lawrence, Newfoundland, 1933-1978 / Richard Rennie -- The Long Road to Action: The Silicosis Problem and Swedish Occupational Health and Safety Policy in the 20th Century / Annette Thörnquist -- Disaster, Meaning Making, and Reform in Antebellum Massachusetts / Patricia Reeve -- Regulating Safety, Regulating Profit: Cost-Cutting, Injury and Death in the British North Sea after Piper Alpha / Dave Whyte -- Courts, Crime, and Workplace / Richard Johnstone -- Blame and Causation in the Aftermath of Industrial Disasters: Nova Scotia's Coal Mines from 1858 to Westray / Susan Dodd -- Accountability and Reform in the Aftermath of the Westray Mine Explosion / Eric Tucker.
Keywords: Government policy; Industrial accidents; Industrial safety; Occupational diseases

Introduction: The Politics of Recognition and Response - Tucker, Eric (Working Disasters: The Politics of Recognition and Response, 2006)
This edited collection draws together original case studies written by leading researchers in Australia, Canada, Great Britain, Sweden, and the United States that examine the politics of working disasters. The essays address two fundamental questions: what gets recognized as a work disaster? And how does the state respond to one? --Publisher's description
Keywords: Government policy; Industrial accidents; Industrial safety; Occupational diseases

Will the Vicious Circle Be Unbroken? The Exclusion of Ontario Farm Workers from the Occupational Health and Safety Act - Tucker, Eric (Precarious Employment: Understanding Labour Market Insecurity in Canada, 2006)
[The author] critically examines the rationale offered to justify the exclusion of agricultural workers from occupational health and safety legislation [in Ontario] which lasted until 2005. The chapter is a case study of marginalized workers denied the benefit of labour law protections. --From editor's introductory chapter, p. 38.
Keywords: Labor Unions; Labor laws and legislation; Labor market; Temporary employment

All That is Solid Melts into Air: Worker Participation and Occupational Health and Safety Regulation in Ontario, 1970-2000. - Storey, Robert; Tucker, Eric (Worker Safety under Siege: Labor, Capital, and the Politics of Workplace Safety in a Deregulated World, 2006)
"[P]rovides a historical analysis of worker participation and occupational health and safety regulation in Ontario from 1970 to 2000 in light of the rise of neoliberal policies. [The authors] describe a shift from systems of mandated partial self-regulation in which workers had to participate, supported by external enforcement of regulations, to more ambiguous models that included the downsizing of government and voluntary compliance by employers." --Editors' introduction. Contents: Acts of God, acts of man: the invisibility of workplace death / Jordan Barab -- Criminal neglect: how dangerous employers stay safe from prosecution / Rory O'Neill -- Regulating risk at work: is expert paternalism the answer to workers irrationality? / Peter Dorman -- Silicosis and the on-going struggle to protect workers's health / Gerald Markowitz and David Rosner -- How safe are U.S. workplaces for Spanish-speaking workers? / Laura H. Rhodes -- Got air? The campaign to improve indoor air quality at the City University of New York / Joan Greenbaum and David Kotelchuck -- State or society? The rise and repeal of OSHA's ergonomics standard / Vernon Mogensen -- The ten-percenters: gender, nationality, and occupational health in Canada / Penney Kome -- All that is solid melts into air: worker participation in Ontario, 1970-2000 / Robert Storey and Eric Tucker -- The sinking of the neoliberal P-36 platform in Brazil / Carlos Eduardo Siqueira and Nadia Haiama-Neurohr -- Health and safety at work in Russia and Hungary: illusion and reality in the transition crisis / Michael Haynes and Rumy Husan.
Keywords: Industrial hygiene; Industrial safety

Precarious Employment and the Law's Flaws: Identifying Regulatory Failure and Securing Effective Protection for Workers - Bernstein, Stephanie; Lippel, Katherine; Tucker, Eric; Vosko, Leah F. (Precarious Employment: Understanding Labour Market Insecurity in Canada, 2006)
This chapter is concerned wtih identifying the many symptoms associated with the inadequacy of workers' protection that the study of precarious employment makes visible. ...[The authors] probe key themes central to regulatory failure in the context of precarious employment, including disparity of treatment between workers in precarious employment and workers with greater security, gaps in legal coverage, the interaction between labour market position and social location, and the lack of compliance and enforcement. --From editor's introductory chapter, p. 37.
Keywords: Labor Unions; Labor laws and legislation; Labor market; Temporary employment